Improving Students’ Reading Comprehension by Using K-W-L (Know, Want to Know, Learned) Strategy - Khofifah Indah Sari; Annisa Astrid; Mirrah Salsabila (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
This study aimed to find out the impacts of the use K-W-L strategy in improving reading comprehension among the twelfth grade students of SMA Mandiri Palembang and to know whether there was a significant difference on reading comprehension between students who were taught using K-W-L strategy and those who were not. This study used quasi-experimental design with non-equivalent pretest-posttest design. The population of the study was the twelfth grade students of SMA Mandiri Palembang, and the sample was taken by using convenience sampling technique. The total number of sample was 54 students, 27 students belonged to experimental group and 27 students belonged to control group. In collecting data, the researcher used test. The test was given twice to experimental and control groups, as a pretest and posttest. The data of students’ pretest and posttest were analyzed by using independent sample t-test and paired sample t-test in SPSS 22 program. The finding showed that the p-output from paired sample t-test 0.000 was lower than 0.05 and t-value 8.985 was higher than t-table with df=26 (1.705). Then, from the independent sample t-test showed that the p-output 0.000 was lower than 0.05 and t-value 5.022 was higher than t-table 1.674. Therefore, it can be concluded that there was a significant difference on students’ reading comprehension achievement who were taught by using K-W-L strategy and those who are not at SMA Mandiri Palembang.